Blind tiger [compact disc, unabridged] - Brown, Sandra, 1948- (Hachette Book Group, 2021)
Thatcher Hutton, a war-weary soldier on the way back to his cowboy life, jumps from a moving freight train to avoid trouble, and lands in more than he bargained for. On the day he arrives in Foley, Texas, a local woman goes missing. Thatcher, the only stranger in town, is suspected of her abduction, and worse. Standing between him and exoneration are a corrupt mayor, a crooked sheriff, a notorious cathouse madam, a sly bootlegger, feuding moonshiners, and a young widow whose soft features conceal an iron will.